2016
DOI: 10.3389/fimmu.2016.00580
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Therapeutic Fc Engineering – Modulation of IgG-Associated Effector Functions and Serum Half-life

Abstract: Today, monoclonal immunoglobulin gamma (IgG) antibodies have become a major option in cancer therapy especially for the patients with advanced or metastatic cancers. Efficacy of monoclonal antibodies (mAbs) is achieved through both its antigen-binding fragment (Fab) and crystallizable fragment (Fc). Fab can specifically recognize tumor-associated antigen (TAA) and thus modulate TAA-linked downstream signaling pathways that may lead to the inhibition of tumor growth, induction of tumor apoptosis, and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 104 publications
3
82
0
Order By: Relevance
“…10 The findings in our study demonstrated that miR-194 decreased inflammation and vascular permeability through TGF-β/SMAD pathway by inhibiting THBS1 so as to provide new idea for the treatment of CIU. 30 In a previous research, scientists found that the level of IgG1 and IgE were lower in patients with chronic urticaria caused by raw fish. Besides, patients with CIU had higher concentration of IgA and lower concentration of IgG and IgM, and higher positive expression rate of THBS1.…”
Section: Discussionmentioning
confidence: 97%
“…10 The findings in our study demonstrated that miR-194 decreased inflammation and vascular permeability through TGF-β/SMAD pathway by inhibiting THBS1 so as to provide new idea for the treatment of CIU. 30 In a previous research, scientists found that the level of IgG1 and IgE were lower in patients with chronic urticaria caused by raw fish. Besides, patients with CIU had higher concentration of IgA and lower concentration of IgG and IgM, and higher positive expression rate of THBS1.…”
Section: Discussionmentioning
confidence: 97%
“…Antibody mAb2 expressing CHO pools were constructed with different effector function silencing mutations, carrying either D265A, P329A (DAPA) or L234A, L235A (LALA) double mutations of the wild‐type human IgG1 in the fragment crystallizable‐part of the antibody heavy chain sequence . Antibodies were purified after 14 days of cell cultivation in shake flasks by protein‐A affinity chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…AvFc's capability to bind to the aforementioned FcgRs was confirmed by flow cytometry using FcgRI-and FcgRIIIa-expressing cells ( Figures 4C and 4D). By contrast, AvFc with an Asn200 / Gln mutation (N200Q-AvFc), which eliminates N-glycosylation in the Fc region corresponding to Asn297 of human IgG 1 and thereby significantly reduces affinity to these FcgRs, 25,26 showed dramatically reduced binding to these receptors ( Figures 4C and 4D; Table 1).…”
Section: The Anti-hiv Activity Of Avfcmentioning
confidence: 99%